Assessing the Effectiveness of Community-Based Oral Health Interventions Using Advanced Dental Materials for Preventing Tooth Decay. - Mahboob, Musa; Shahzad, Aamir; Khurram, Maleeha; Khan, Nida; Suhaib, Fatima; Saba, Kiran (Journal of Neonatal Surgery, 2025)
Objective: To determine the efficacy of community-based oral health programs using advanced dental materials in the prevention of tooth decay in the local population. Methodology: The study was a cross-sectional one carried out at a given number of community health centers and schools. A non-probability consecutive sampling method was used to select 419 participants. Structured questionnaires and oral examination were used in the collection of data according to WHO criteria. Data on oral care behaviors, community activity involvement, and the use of state-of-the-art dental supplies were documented. SPSS version 26 was used in the analysis of the data. Frequencies and percentages were used to represent descriptive statistics, and chi-square and t-tests were used to test the associations between preventive interventions and caries prevalence, with p ≤0.05 regarded as significant. Results: Out of the participants, 66.3 percent had participated in community-based oral health programs, and 46.8 percent had been administered fluoride varnish or sealant applications. The general level of dental caries was 38.4%. The prevalence of caries was significantly lower in those who had fluoride varnish or sealants (29.6%) than in those who lacked them (53.2%) (p < 0.001). Conclusion: Oral health interventions at the community level with advanced dental materials are effective in preventing dental caries and enhancing oral health outcomes. The growth of such preventive measures can be critical in ensuring population-wide oral health, especially in low-resource conditions.